Cooperative learning : Teori, riset dan praktik / Robert E. Slavin ; penerjemah Narulita Yusron ; penyunting Zubaedi. - SLAVIN, Robert E.; Nurulita Yusron; Zubaedi (Nusa Media, 2011)
x, 348 hlm. : ilus. ; 23 cm